MILITARY STRATEGY OF INDIA - M. S. Zaitsev (Vestnik MGIMO-Universiteta, 2017)
The article analyzes the evolution of military strategy of the Republic of India and key factors that influences its development. New Delhi keeps an eye on the balance of power in South Asia to create favorable conditions for its economic and social development, yet the remaining threats and new challenges still undermine the security and stability in India. The ambitions of China aspiring to power in Asia-Pacific region, combined with its immense military build-up and territorial disputes, cause disturbance in New Delhi. The remaining tensions between India and Pakistan also cause often border skirmishes and medium-scale conflicts. Close relations between China and Pakistan, labeled as “all-weather friendship”, are a source of major concern for India. The fact that both Beijing and Islamabad wield nuclear weapons means that without effective mechanisms of nuclear deterrence any military conflict may turn into a full-scale nuclear war. Terrorist activities and insurgency in the Indian state of Jammu and Kashmir and in the North-Eastern regions of the country, along with maritime piracy and illicit drug trafficking contribute to the complicated nature of the challenges to the Indian security. Indian military strategy is considered as a combination of the army doctrine, maritime doctrine and nuclear doctrine. The Indian political and military leadership wants to meet the challenges of changing geopolitical environment and thus continuously adapts its strategy. However, there is still a gap between theory and practice: Indian armed forces lack the capacity to implement the declared goals because of bulky bureaucratic system, outdated military equipment and insufficient level of command and control. The government needs to mobilize political will and administrative resources to upgrade its defense sector to counter its security threats and challenges.